Auditor Sensitivity to Real Earnings Management: The Importance of Ambiguity and Earnings Context - Commerford, Benjamin P.; Hermanson, Dana R.; Houston, Richard W.; Peters, Michael F. (Contemporary Accounting Research, 2019)
ABSTRACT Differentiating real earnings management (REM) from normal business decisions poses a unique challenge for auditors, researchers, and investors. The ambiguity associated with REM, and the fact that REM does not violate GAAP, may explain why its use is on the rise. While some assert that auditors are not, and should not be, concerned with REM, recent research suggests that REM may influence some auditor judgments. Using Correspondent Inference Theory (CIT) as our theoretical framework, we extend REM research by investigating the ways in which auditors respond to REM and how auditors deal with the intrinsic ambiguity associated with REM. We administer a 3×2 between‐subjects experiment to 113 highly‐experienced auditors, manipulating the level of ambiguity surrounding the observed REM (Explicit REM, Potential REM, or No REM) and the earnings context in which the client engages in REM (the client beat or missed the consensus earnings forecast). We find that auditors respond to REM by lowering assessments of management tone (i.e., management's commitment to a culture of high ethical standards), being more likely to discuss the issue with the audit committee, and being less likely to retain the client. Auditors respond to Explicit REM regardless of the earnings context, but respond to Potential (i.e., ambiguous) REM only when the client beats the forecast. Finally, we find that management tone mediates the relation between REM and auditor responses, even after controlling for various audit‐related risks. Thus, for auditors, REM appears to be primarily a “people” issue, as REM provides a negative signal about management.